The epigenetic circle: feedback loops in the maintenance of cellular memory - Marko Tomljanović; Cita Hanif Muflihah; Dejan Rajkovski; Pawel Mikulski (Epigenetics & Chromatin)
Abstract The memory of gene expression states, active or repressive, is a fundamental biological concept as it controls cell fate in development, immunity and abiotic stress responses. Such memory is maintained through cell division as a cornerstone of epigenetics. Cell division poses a threat to the stability of epigenetic memory as memory-encoding factors become diluted between daughter cells. Thus, long-term epigenetic memory must depend on the feedback loops to sustain it over cell generations. Despite a widespread presence and fundamental importance, maintenance mechanisms of epigenetic memory are far from being clear. Here, we summarize present knowledge about feedback loops that allow maintenance of epigenetic information. We describe conceptually distinct, cis- and trans-, feedback loops, which rely on local, read-write propagation mechanisms or regulatory loops of diffusible factors, respectively. Furthermore, we provide cases of their frequent coupling in epigenetic systems in cells and synthesize current challenges in understanding feedback mechanisms. Overall, we believe this review to benefit the scientific community in bringing a holistic perspective on such fundamental biological phenomenon.